Talking to terrorists: how to end armed conflicts - Powell, Jonathan (The Bodley Head, 2014)
Introduction -- Why we must talk to terrorists -- Making contact with the enemy -- Building a channel -- How governments engage with terrorists -- The third party -- Starting a negotiation -- The art of negotiation -- Why do some negotiations succeed and others fail? -- Only implementation creates trust -- The lessons of history -- The future